2018
DOI: 10.1038/s41598-018-19778-0
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan hydroxylase (TRH) loss of function mutations induce growth and behavioral defects in Daphnia magna

Abstract: Tryptophan hydroxylase (TRH) is the rate limiting enzyme in the serotonin synthesis. CRISPR-Cas9 technology was used to generate seven indel TRH mutants in Daphnia magna. Mono-allelic indel TRH−/+ clones showed normal levels of serotonin, measured by both immunohistochemistry and mass spectrometry (LC-MS/MS), whereas bi-allelic indel TRH−/− clones showed no detectable levels of serotonin. Life history and behavioral responses of TRH−/− clones showed the anti-phenotype of those exposed to selective serotonin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…magna individuals chronically exposed to low levels of fluoxetine had higher amounts of serotonin in the brain and reproduced to a greater extent . Conversely, individuals having the tryptophan hydrolase gene mutated (which is the rate-limiting enzyme for serotonin biosynthesis) lacked serotonin and showed decreased growth and reproductive rates . In the present study, genes belonging to the dopaminergic and serotonin signaling pathways were particularly enriched in cluster B followed by clusters A and C in decreasing order.…”
Section: Discussionmentioning
confidence: 41%
“…magna individuals chronically exposed to low levels of fluoxetine had higher amounts of serotonin in the brain and reproduced to a greater extent . Conversely, individuals having the tryptophan hydrolase gene mutated (which is the rate-limiting enzyme for serotonin biosynthesis) lacked serotonin and showed decreased growth and reproductive rates . In the present study, genes belonging to the dopaminergic and serotonin signaling pathways were particularly enriched in cluster B followed by clusters A and C in decreasing order.…”
Section: Discussionmentioning
confidence: 41%
“…Fluoxetine enhances brain serotonin activity in Daphnia (Campos et al, 2016), increases development and reproductive rates (Campos et al, 2012) and alters phototaxis behavior. Recent studies using knockout Daphnia individuals lacking serotonin showed that these animals had the opposite phenotype as those exposed to fluoxetine: animals matured latter, reproduced less and were more mobile than wild type animals (Rivetti et al, 2018). There is thus a neurofunctional link between fluoxetine, its pharmacological target serotonin and effects (life-history and behavioral changes).…”
Section: Discussionmentioning
confidence: 99%
“…(3) Role of hubgenes: on a functional level, recent advantages in molecular techniques now allow for a detailed testing of network structures to confirm if molecular cascades collapse when predicted hub-genes are modified via gene editing approaches (e.g., RNAi or CRISPr and Talen techniques 59-61 ).…”
Section: Discussionmentioning
confidence: 99%